Obesity treatment by epigallocatechin‐3‐gallate−regulated bile acid signaling and its enriched Akkermansia muciniphila. Issue 12 (8th June 2018) - Sheng, Lili; Jena, Prasant Kumar; Liu, Hui‐Xin; Hu, Ying; Nagar, Nidhi; Bronner, Denise N.; Settles, Matthew L.; Baümler, Andreas J.; Wan, Yu‐Jui Yvonne
ABSTRACT: Dysregulated bile acid (BA) synthesis is accompanied by dysbiosis, leading to compromised metabolism. This study analyzes the effect of epigallocatechin‐3‐gallate (EGCG) on diet‐induced obesity through regulation of BA signaling and gut microbiota. The data revealed that EGCG effectively reduced diet‐increased obesity, visceral fat, and insulin resistance. Gene profiling data showed that EGCG had a significant impact on regulating genes implicated in fatty acid uptake, adipogenesis, and metabolism in the adipose tissue. In addition, metabolomics analysis revealed that EGCG altered the lipid and sugar metabolic pathways. In the intestine, EGCG reduced the FXR agonist chenodeoxycholic acid, as well as the FXR‐regulated pathway, suggesting intestinal FXR deactivation. However, in the liver, EGCG increased the concentration of FXR and TGR‐5 agonists and their regulated signaling. Furthermore, our data suggested that EGCG activated Takeda G protein receptor (TGR)‐5 based on increased GLP‐1 release and elevated serum PYY level. EGCG and antibiotics had distinct antibacterial effects. They also differentially altered body weight and BA composition. EGCG, but not antibiotics, increased Verrucomicrobiaceae, under which EGCG promoted intestinal bloom of Akkermansia muciniphila . Excitingly, A. muciniphila was as effective as EGCG in treating diet‐induced obesity. Together, EGCG shifts gut microbiota and regulates BA signaling thereby having a metabolic beneficial effect.—Sheng, L., Jena, P. K., Liu, H.‐X., Hu, Y., Nagar, N., Bronner, D. N., Settles, M. L., Baumler, A. J., Wan, Y.‐J. Y. Obesity treatment by epigallocatechin‐3‐gallate−regulated bile acid signaling and its enriched Akkermansia muciniphila . FASEB J. 32, 6371–6384 (2018). www.fasebj.org